Caractéristiques écologiques de la galerie forestière de la rivière Kossi dans les communes de Dassa-Zoumé et de Glazoué au Centre-Bénin - Dissou, Florent Essin; Adjakpa, Jacques Boco; Tchabi, Isidore Vincent; Toundoh, Paul Oluwafèwa; Obossou, Frida Kobayé (European Scientific Journal, ESJ, 2018)
This study concerns characteristics of forest gallery of Kossi River in municipalities of Dassa-Zoumé and Glazoué in the Department of Hills. The study of structure and floristic diversity of gallery forest of Kossi River was done by phytoecological method in 41 plots of 2,500 m² (50 m × 50 m) for study of plants groups and plots of 25 m² (5 m × 5 m) for régénération. In total, 82 species left in 68 genders and 28 families were identified. The analysis of the 41 plots by the Detrended Canonical Analysis (DCA) shown 03 plant groups such as Anogeissus leiocarpa and Daniellia oliveri group plant, Anogeissus leiocarpa and Isoberlinia doka group, and Cynometra megalophylla and Ceiba pentandra group. Specie richness of these plant groups varies from 31 to 41 species (dbh ≥ 10 cm). Families diversity is between 21 and 22 with predominance of Moraceae, LeguminosaeCaesalpinoideae and Leguminosae-Mimosoideae. Shannon diversity index varies from 2.4 to 3.1 bits and Pielou equitability from 0.5 to 0.6. Density varies from 129 to 233 stems / ha, basal area from 7.9 to 17.2 m² / ha and regeneration rate by group plants varies from 21.60 % to 42.96 %.